2018
DOI: 10.1101/245761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic architecture of gene expression traits across diverse populations

Abstract: For many complex traits, gene regulation is likely to play a crucial mechanistic role. How the genetic architectures of complex traits vary between populations and subsequent effects on genetic prediction are not well understood, in part due to the historical paucity of GWAS in populations of non-European ancestry. We used data from the MESA (Multi-Ethnic Study of Atherosclerosis) cohort to characterize the genetic architecture of gene expression within and between diverse populations. Genotype and monocyte ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 56 publications
(112 reference statements)
6
82
0
Order By: Relevance
“…23 However, genetic architectures of gene expression differ across diverse populations. 12,56,57 Thus, SEG annotations derived from gene expression data from diverse populations may provide additional insights into population-specific causal effect sizes. Fourth, we restricted our analyses to SNPs that were relatively common (MAF>5%) in both populations, due to the lack of a large LD reference panel for East Asians.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, genetic architectures of gene expression differ across diverse populations. 12,56,57 Thus, SEG annotations derived from gene expression data from diverse populations may provide additional insights into population-specific causal effect sizes. Fourth, we restricted our analyses to SNPs that were relatively common (MAF>5%) in both populations, due to the lack of a large LD reference panel for East Asians.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether these models can be informative in African American women and other groups. Recent findings have suggested that stratification by race or ancestry may be necessary to construct proper tests of association across race or ancestry [17, 18]. However, many cohorts, especially large-scale genetic cohorts, may not have a sufficient sample size in minority populations to power these tests.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the genetic architecture of schizophrenia in African Americans, we performed transcriptome-wide association studies using prediction models built in 55 tissues. In the GAIN cohort of 2,256 individuals (969 controls and 1287 cases), we predicted gene expression across 48 tissues in GTEx, six models built from monocytes across MESA, and DLPFC from CommonMind (Barbeira et al, 2018; Wheeler et al, 2016; Mogil et al, 2018; Huckins et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Version 7 of the GTEx predictors we used contain data exclusively from individuals of European descent. These models are not optimal for predicting expression in African American cohorts (Mogil et al, 2018; Mikhaylova and Thornton, 2019). While they offer power driven by sample size, they do not include models with African ancestry-specific alleles that might affect susceptibility to neuropsychiatric traits in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation